Hepatitis C seropositivity and RNA detection among Type2 Diabetic patients in Sulaimani Governorate-Iraqi Kurdistan Region - Hama, Salih A. (Sulaimani Journal for Pure and Applied Sciences, 2016)
The current study included 421 cases (221 with type 2 diabetic) and (200 non-diabetics- control group). ELISA and conventional PCR techniques were used for detection of anti-HCV antibodies and HCV-RNA respectively. The percentage rates of HCV seropositivity were (9.5%) among type 2 diabetic patients that were significantly higher (p < 0.05) compared to controls. Moreover, HCV-RNA detection was more frequent among diabetic patients (5.88%), although no significant differences found with non-diabetic cases (p > 0.05). No significant effects of sex found among positive results (p > 0.05). Duration of diabetes, residence, the job type, the patient’s education level, history of jaundice, smoking and alcohol consumption showed significant effects (p < 0.05) on the percentage rates of HCV infection among type 2 diabetic patients. It was concluded that these parameters are a risk factor for HCV infection among Type 2 Diabetic patients. Moreover, diabetes itself can consider as a risk factor for HCV infection.
Keywords: HCV; Type 2 diabetic; seropositivity; HCVRNA; antiHCV antibodies